2018
DOI: 10.1080/02656736.2018.1508757
|View full text |Cite
|
Sign up to set email alerts
|

High intensity focused ultrasound (HIFU) for the treatment of symptomatic breast fibroadenoma

Abstract: US-guided HIFU is an effective procedure and a minimally invasive alternative for the treatment of breast FA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 33 publications
3
37
0
Order By: Relevance
“…Three previous European studies have shown reduction in fibroadenoma volume from 43.2% to 89% 6‐8 . Our study echoed with similar finding with volume reduction of 62% at 12th month post‐HIFU.…”
Section: Hahn Et Al 2018 Peek Et Al 2016supporting
confidence: 91%
See 1 more Smart Citation
“…Three previous European studies have shown reduction in fibroadenoma volume from 43.2% to 89% 6‐8 . Our study echoed with similar finding with volume reduction of 62% at 12th month post‐HIFU.…”
Section: Hahn Et Al 2018 Peek Et Al 2016supporting
confidence: 91%
“…HIFU has been used in treating different solid tumors, 2,3 and its use in breast fibroadenoma has been described in only a few European studies (Table 1). 6‐8 …”
Section: Hahn Et Al 2018 Peek Et Al 2016mentioning
confidence: 99%
“…Breast fibroadenomas (FA) are the most common benign tumors, which account for about 70% of benign breast lesions. 46 They usually affect females in the reproductive period who have no other obvious symptoms except for a palpable breast lump during self-examination, occasionally associated with breast pain. A large number of patients choose breast-conserving therapy.…”
Section: Clinical Applications Of Hifumentioning
confidence: 99%
“…In addition, breast fibroadenoma is another indication that can be treated using the EchoPluse® system. A clinical trial was conducted where patients were treated at intensity of 40 W for 38 min under local anesthesia, a success rate of 89% was reported (22).…”
Section: Ablation Of Thyroid Nodules and Breast Fibroadenomasmentioning
confidence: 99%